Complete tumor necrosis after neoadjuvant chemotherapy defines good responders in patients with Ewing sarcoma. Issue 1 (28th October 2022) - Lozano‐Calderón, Santiago A.; Albergo, Jose Ignacio; Groot, Olivier Q.; Merchan, Nelson A.; El Abiad, Jad M.; Salinas, Vanessa; Gomez Mier, Luis Carlos; Montoya, Camilo Soto; Ferrone, Marco L.; Ready, John E.; Linares, Francisco J.; Levin, Adam S.; et al.
Abstract: Background: Survival in patients who have Ewing sarcoma is correlated with postchemotherapy response (tumor necrosis). This treatment response has been categorized as the response rate, similar to what has been used in osteosarcoma. There is controversy regarding whether this is appropriate or whether it should be a dichotomy of complete versus incomplete response, given how important a complete response is for in overall survival of patients with Ewing sarcoma. The purpose of this study was to evaluate the impact that the amount of chemotherapy‐induced necrosis has on (1) overall survival, (2) local recurrence‐free survival, (3) metastasis‐free survival, and (4) event‐free survival in patients with Ewing sarcoma. Methods: In total, 427 patients who had Ewing sarcoma or tumors in the Ewing sarcoma family and received treatment with preoperative chemotherapy and surgery at 10 international institutions were included. Multivariate Cox proportional‐hazards analyses were used to assess the associations between tumor necrosis and all four outcomes while controlling for clinical factors identified in bivariate analysis, including age, tumor volume, location, surgical margins, metastatic disease at presentation, and preoperative radiotherapy. Results: Patients who had a complete (100%) tumor response to chemotherapy had increased overall survival (hazard ratio [HR], 0.26; 95% CI, 0.14–0.48; p < .01), recurrence‐free survival (HR, 0.40; 95% CI, 0.20–0.82; p = .01), metastasis‐free survival (HR, 0.27; 95% CI, 0.15–0.46; p ≤ .01), and event‐free survival (HR, 0.26; 95% CI, 0.16–0.41; p ≤ .01) compared with patients who had a partial (0%–99%) response. Conclusions: Complete tumor necrosis should be the index parameter to grade response to treatment as satisfactory in patients with Ewing sarcoma. Any viable tumor in these patients after neoadjuvant treatment should be of oncologic concern. These findings can affect the design of new clinical trials and the risk‐stratified application of conventional or novel treatments. Abstract : Complete tumor necrosis should be the index parameter to grade response to treatment as satisfactory in patients with Ewing sarcoma. Any viable tumor in these patients after neoadjuvant treatment should be of oncologic concern, and these findings can affect the design of new clinical trials and the risk‐stratified application of conventional or novel treatments.